(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
An explicit reference to the interest of future generations has been introduced in Article 9 of the Constitution of Italian Republic by Constitutional Law No. 1/2022. Such amendment renews the need to define the frame of this new constitutional content in order to highlight the resolution of some fundamental and essential issues, such as: the problem of the existence of future generations, their eligibility to assume legal positions, the anatomy of the interest that the Italian Constitution recognizes them, as well as the prospects of judicial protection.